BREASTFEEDING AND OVERWEIGHT IN PRESCHOOL CHILDREN - Aparício, Graça (2013)
Background: Scientific evidence shows that breastfeeding has a protective effect on the development of excess weight. Objectives: To determine the effect of breastfeeding on overweight children. Methods: Cross-sectional and observational study comprising 1424 preschool children, average age 4,58 years old (SD=0,990), residents in the centre/north region of Portugal. Children’s anthropometric measurement was obtained and the classification was based on NCHS reference (CDC, 2000) and the birth weight classification on WHO (2001). Results: A total of 1193 children were breastfed and 451 (37.9%) were overweight, i.e. breastfeeding proved to be protective in 60% of the cases. In the 451 children who were breastfed and overweight, the average age of the mother was 34.27 old (SD = 5.51) and the mean BMI was 25.03 (SD = 4.30). 23 mothers were diagnosed with gestational diabetes (5.1%) and at birth, 6.2% presented themselves quite large, 4.2% lightweight and 89.6% normal for gestational age. In these children, the duration of breastfeeding was ≤3 months in 34%, between 4-6 months in 30.70%, between 7-12 months in 20.4% and ≥13 months in 14.9%. Excess weight was higher in children with a breastfeeding duration of ≤3 months (KW OM = 244.43) and ≥13 months (KW OM = 249.39) (x2 = 19.180, p = 0.000, df = 3). The period of lactation had an effect on the nutritional status of children, explaining 50.0% of its variance. Conclusion: The results suggest significant effect of breastfeeding on the development of later overweight, justifying the creation favourable conditions for its promotion.